25th AIAA/CEAS Aeroacoustics Conference 2019
DOI: 10.2514/6.2019-2564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grazing Flow on Grooved Over-the-Rotor Acoustic Casing Treatments

Abstract: After testing grooved over-the-rotor acoustic casing treatments on a turbofan rotor, a follow-on study was performed to investigate the effect of flow on grooved acoustic liners. The experiment was performed to understand the scaling of acoustic liner absorption with grazing flow and investigate a potential noise source from grooved acoustic liners. Acoustic liner absorption and reflection characteristics were quantified by examining the reduction in amplitude of a plane wave traveling over 2 inch liners with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…is the mode number, L is the cavity width, α = 0.25 is the empirical constant which increases as L/D increases, K c is the ratio of the vortex convection speed across the liner cavity face sheet to the free-stream velocity, and M is the free-stream Mach number. Unlike the case of Eq.3 proposed by Rossiter, Block [24] has shown that the self-sustained oscillation frequencies in deep cavities are also sensitive to the L/D ratio of the cavity in addition to the Mach number, and it is given by [25],…”
Section: Liner Self-noisementioning
confidence: 99%
“…is the mode number, L is the cavity width, α = 0.25 is the empirical constant which increases as L/D increases, K c is the ratio of the vortex convection speed across the liner cavity face sheet to the free-stream velocity, and M is the free-stream Mach number. Unlike the case of Eq.3 proposed by Rossiter, Block [24] has shown that the self-sustained oscillation frequencies in deep cavities are also sensitive to the L/D ratio of the cavity in addition to the Mach number, and it is given by [25],…”
Section: Liner Self-noisementioning
confidence: 99%
“…3 Testing of the same OTR casing treatments in the NASA Grazing Flow Impedance Tube showed the generation of cavity noise at the same frequency range than when installed over a turbofan rotor. 14 The lengthwise tones caused by the feedback loop of the unstable shear layer over the cavity 15 cannot be predicted in the analytical groove impedance model nor the FEM solver due to the inviscid nature of the Helmholtz equation and it is out of the scope of this work.…”
Section: Application To Otr Liners: Multiple Grooves Excited By a Poimentioning
confidence: 99%
“…After testing grooved OTR acoustic casing treatments on a turbofan rotor (see next sections), a follow-on study was performed to investigate the effect of flow on grooved acoustic liners. 46 The experiment was performed to understand the scaling of acoustic liner absorption with grazing flow and to investigate the source of selfnoise due to the grooved liner. Six configurations were tested in the GFIT, matching those that were tested in the ANCF and W-8.…”
Section: Uniform-depth Concept With and Without Embedded Expansion Chambersmentioning
confidence: 99%